The significance of notch signaling in the regulation of Тreg-lymphocyte differentiation in patients with infiltrative pulmonary tuberculosis - A. E. Sanina; V. A. Serebryakova; O. I. Urazova; A. A. Gadzhiev; Т. E. Kononova (Медицинская иммунология)
Data on the role of regulatory T lymphocytes (Treg) in the immunopathogenesis of tuberculosis are actively accumulating in the current literature. The overwhelming effect of Treg cells on the proliferation, functional activity of Th1 lymphocytes and antigen-presenting cells allows to consider this population as a possible target of modulation of the immune response in patients with tuberculosis. The Notch signaling pathway participates in the regulation of FoxP3 transcription factor expression and, therefore, is capable of supporting suppressor activity of Treg lymphocytes. A key role in the functioning of the Notch signaling cascade belongs to the enzyme γ-secretase that cleaves the intracellular domain of the receptor (Notch ICD), with the subsequent formation of a complex that regulates cell differentiation. The actively studied inhibitor of γ-secretase is DAPT – N-[N-(3.5-difluorophenacetyl)-L-alanyl]-S-phenylglycine tert-butyl ester). Mononuclear leukocytes isolated from the blood of patients with drug-sensitive and drug-resistant pulmonary tuberculosis by gradient centrifugation before the start of anti-tuberculosis therapy were used as the material for the study. The cells were cultured under conditions of stimulation with Mycobacterium tuberculosis antigens CFP10-ESAT6 or with the addition of γ-secretase inhibitor (DAPT) at doses of 5 μM/L and 10 μM/L in combination with CFP10-ESAT6 at 37 °C and 5% CO2 for 72 h to the incubation medium. The number of Treg lymphocytes was assessed by flow cytofluorimetry by determining the expression of the CD4 surface receptor (FITC) and the intracellular transcription factor FoxP3 (PE). In intact cell cultures of pulmonary tuberculosis patients, the relative number of Treg lymphocytes was statistically significantly (p < 0.001) higher than that of healthy donors. Stimulation of cells with CFP10-ESAT6 antigens was accompanied by an increase in the proportion of CD4+FoxP3+ cells in both groups of tuberculosis patients. Addition of γ-secretase inhibitor at a concentration of 5 μM/L to the incubation medium did not lead to statistically significant changes in the number of Treg lymphocytes. The increase in DAPT concentration up to 10 μM/L was accompanied by a decrease in the number of Treg lymphocytes in comparison with the corresponding indices upon stimulation with CFP10-ESAT6 antigens in all groups of the subjects. Regardless of cultivation conditions, the number of CD4+FoxP3+ cells in patients with drug-resistant mycobacteria exceeded their number in patients with drug-sensitive pulmonary tuberculosis. Inhibition of the Notch signaling pathway by a γ-secretase inhibitor (DAPT) at a concentration of 10 μM/L contributed to a decrease in the number of Treg lymphocytes in patients with drug-sensitive and drug-resistant pulmonary tuberculosis. Reduction of Treg lymphocyte number by γ-secretase inhibitor confirms the importance of Notch signaling cascade as a potential target for correction of Treg lymphocytes immunosuppressive activity and pathogenetic therapy of tuberculosis.